Monetary Orientalism: Currency Wars and the Framing of China as Global Cheater. Issue 4 (2nd October 2019) - Bui, Long T.
Abstract : China stands as a paradigmatic sign of deep angst for the United States in late stage capitalism, a menacing spectre of foreignness and otherness that organises Western popular anxieties at a time where nothing is fixed within international markets. Focusing on the so called "currency wars" debate that erupted in the early twenty-first century, when the PRC was accused of devaluating its currency, this article contends that PRC's representation as a prime currency manipulator and cheater can be conceptualised through what I am calling monetary Orientalism or the ways imperialising thoughts circulate around monetary flows in relation to a rising Asiatic superpower. This framework serves as a prime lens for situating US nationalist sentiment and its sense of an exceptional global self against what it perceives as a global other.